2013
DOI: 10.1136/bmjopen-2012-002326
|View full text |Cite
|
Sign up to set email alerts
|

Quality of newborn care: a health facility assessment in rural Ghana using survey, vignette and surveillance data

Abstract: ObjectiveTo assess the structural capacity for, and quality of, immediate and essential newborn care (ENC) in health facilities in rural Ghana, and to link this with demand for facility deliveries and admissions.DesignHealth facility assessment survey and population-based surveillance data.SettingSeven districts in Brong Ahafo Region, Ghana.ParticipantsHeads of maternal/neonatal wards in all 64 facilities performing deliveries.Main outcome measuresIndicators include: the availability of essential infrastructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
48
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 29 publications
5
48
2
1
Order By: Relevance
“…The results of this study are similar to previous studies in low-income settings in terms of the lack of staff and essential equipment, 29 particularly in public facilities. [30][31][32] However, there were differences in the criteria used in assessing the quality of care compared with those used in a previous study, 24 that is, differences in number of signal functions for each category, no distinction of regular versus skilled health professionals, and no use of nonmedical functions.…”
Section: Discussionsupporting
confidence: 82%
“…The results of this study are similar to previous studies in low-income settings in terms of the lack of staff and essential equipment, 29 particularly in public facilities. [30][31][32] However, there were differences in the criteria used in assessing the quality of care compared with those used in a previous study, 24 that is, differences in number of signal functions for each category, no distinction of regular versus skilled health professionals, and no use of nonmedical functions.…”
Section: Discussionsupporting
confidence: 82%
“…Previous clinical observational studies in Ghana,15 the Philippines,8 Nepal32 and Bangladesh33 have also identified gaps in the quality of newborn healthcare. A health facility assessment in rural Ghana highlighted major gaps in newborn care equipment and quality of newborn care as well as the importance of quality improvement 15.…”
Section: Discussionmentioning
confidence: 99%
“…A health facility assessment in rural Ghana highlighted major gaps in newborn care equipment and quality of newborn care as well as the importance of quality improvement 15. A recent study in the Philippines also found that bathing of the baby in the first 24 hours was common and placing the baby skin-to-skin was infrequent 8.…”
Section: Discussionmentioning
confidence: 99%
“…Newhints was able to build on a pre-existing group of lay health volunteers who were willing and able to expand their role and whom community members were willing to accept as counsellors in newborn care. Rates of key positive behaviours for newborn health, including facility-based births, were already fairly high at baseline, whereas the quality of newborn care in health facilities was poor 3, 39. The cost of increased use of health facilities attributable to Newhints was extremely low because only a few babies for whom care was sought were admitted to hospital, and because in our setting, the strategy did not increase usage rates for other services.…”
Section: Discussionmentioning
confidence: 74%